Stochastic non-linear oscillator models of EEG: the Alzheimer's disease case - Ghorbanian, Parham; Ramakrishnan, Subramanian; Ashrafiuon, Hashem (Frontiers in Computational Neuroscience, 2015)
In this article, the Electroencephalography (EEG) signal of the human brain is modeled as the output of stochastic nonlinear coupled oscillator networks. It is shown that EEG signals recorded under different brain states in healthy as well as Alzheimer's disease (AD) patients may be understood as distinct, statistically significant realizations of the model. EEG signals recorded during resting eyes-open (EO) and eyes-closed (EC) resting conditions in a pilot study with AD patients and age-matched healthy control subjects (CTL) are employed. An optimization scheme is then utilized to match the output of the stochastic Duffing - van der Pol double oscillator network with EEG signals recorded during each condition for AD and CTL subjects by selecting the model physical parameters and noise intensity. The selected signal characteristics are power spectral densities in major brain frequency bands Shannon and sample entropies. These measure allow matching of linear time varying frequency content as well as nonlinear signal information content and complexity. The main findings of the work is that statistically significant unique models represent the EC and EO conditions for both CTL and AD subjects. However, it is also shown that the inclusion of sample entropy in the optimization process, to match the complexity of the EEG signal, enhances the stochastic nonlinear oscillator model performance.